A case report of atrial enlargement and transitory electrocardiographic changes during labour - Antonio VILLA; Donatella RODEGHER; Valeria BARBERA; Carlo TURRI (Journal of Health and Social Sciences)
During pregnancy some aspecific physiological electrocardiographic changes are described in literature. We report a case of a young pregnant aged 32 who showed, during labour at 39 weeks, electrocardiogram signs of biatrial enlargement resolved post-partum. The cardiovascular system is subject to a reversible series of structural and functional adaptations during pregnancy. Emergency physicians, gynecologists and obste- tricians should be aware of these physiological electrocardiographic changes during pregnancy in order to obtain a correct and an appropriate diagnosis in emergency room.